Livros didáticos para o ensino de português como língua estrangeira sob uma perspectiva intercultural : diferenças entre Brasil e Itália - Smith, James Rocha (2023)
The intercultural communicative approach to language teaching has been promoted worldwide since the 1970s, thanks to advances in Applied Linguistics studies. Thus, linguists and publishers started mobilizing for the creation of didactic materials that considered the cultural element associated with language learning. In Brazil, during the 1980s, the production of Brazilian Portuguese textbooks showed considerable growth, with textbooks that can still be found in bookstores today. In view of this, this paper aims to analyze two of the textbooks used in Brazil and Italy for teaching PFL (Portuguese as a Foreign Language), in immersion and non-immersion contexts, aligned with the intercultural communicative approach in their practices. This is documental research that seeks to deduce from the corpus constituted by the pedagogical practices indicated in the two didactic resources the proposals that deal with cultural/intercultural aspects. Since this is qualitative research, the results can be used as a reference for other investigations and teaching practices that are interested in the analysis of PFL textbooks in contemporary use. Moreover, this dissertation intends to present reflections that may collaborate with the choice of materials by teachers who are looking for books to promote the learning of a new language, which includes understanding the cultural characteristics, as well as the mechanisms that make it possible to produce linguistic-discursive expressions adequate to each communicative situation. Specifically, it was observed that the book published in Brazil provides questions about cultural aspects, through moments of discussion about Brazilian culture. The book published in Italy, on the other hand, seems to require a greater effort from the teacher to create moments of discussion about Brazilian culture. In both, with greater relevance in the Brazilian book, the analysis of terms that refer to aspects related to this culture has a prominent role in the exercises analyzed. From the reflections elaborated, in the continuity of the research, it will also be possible to contribute with the comparison with other books in circulation and with the didactic organization of practices that can be planned to articulate theory and practice in the analysis and understanding of the possible ways for the development of the intercultural perspective to be effective in the teaching of PFL.